2016
DOI: 10.1016/j.neuroscience.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Altered vesicular glutamate transporter distributions in the mouse cochlear nucleus following cochlear insult

Abstract: Vesicular glutamate transporters 1 and 2 (VGLUT1 and VGLUT2) have distinct distributions in the cochlear nucleus that correspond to the sources of the labeled terminals. VGLUT1 is mainly associated with terminals of auditory nerve fibers, whereas VGLUT2 is mainly associated with glutamatergic terminals deriving from other sources that project to the cochlear nucleus (CN), including somatosensory and vestibular terminals. Previous studies in guinea pig have shown that cochlear damage results in a decrease of VG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 54 publications
(92 reference statements)
4
25
0
Order By: Relevance
“…Previous studies have demonstrated loss of auditory nerve inputs in the VCN after acoustic overexposure (Kim et al, 2004), surgical destruction of the cochlea (Fyk-Kolodziej et al, 2011), and application of ototoxic substances (Zeng et al, 2009, Yuan et al, 2014, Heeringa et al, 2016), but the effects of other types of HC loss on the VCN are not well characterized. To evaluate stereological changes in the VCN after DT-induced HC loss, we prepared transverse sections (N = 6 animals for each group) stained with cresyl violet and assessed the total volume, neuron density, and cell size in the VCN (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated loss of auditory nerve inputs in the VCN after acoustic overexposure (Kim et al, 2004), surgical destruction of the cochlea (Fyk-Kolodziej et al, 2011), and application of ototoxic substances (Zeng et al, 2009, Yuan et al, 2014, Heeringa et al, 2016), but the effects of other types of HC loss on the VCN are not well characterized. To evaluate stereological changes in the VCN after DT-induced HC loss, we prepared transverse sections (N = 6 animals for each group) stained with cresyl violet and assessed the total volume, neuron density, and cell size in the VCN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…VGLUT1 immunocytochemistry and quantification were conducted as described previously (Zhou et al, 2007, Heeringa et al, 2016). Sections were incubated for 30 minutes in a blocking solution containing 1% normal goat serum in PBS with 0.3% Triton X-100 followed by overnight incubation with primary antibody, anti-VGLUT1 (rabbit anti-VGLUT-1, Synaptic Systems, Germany), diluted in blocking solution 1:2000 for 18 hours at RT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is a consequence of an increase in glutamatergic neurotransmission from somatosensory fibers following loss of input from auditory pathways [102]. Interestingly, the upregulation of glutamatergic inputs from the somatosensory system occurs after a ‘threshold’ level of cochlear damage, beyond which, no further changes occur [103]. Tinnitus-related changes in auditory-somatosensory integration by the fusiform cells include increased long-term potentiation [41], likely mediated by the increased non-auditory glutamatergic innervation after cochlear damage [75, 76].…”
Section: Role Of Non-auditory Structuresmentioning
confidence: 99%
“…For the auditory system, it was shown that the peripheral loss of response to sensory stimuli due to traumatic events, aging processes or genetic defects among others triggers central gain adjustment in order to re-stabilize the network through a disproportional elevation of the neuronal firing rate [31,82,83]. How target neurons of auditory nerve fibers, likely to be present in the dorsal [59] [85] may participate in generation of compensating central hyperactivity. Indeed, Gα-Gβγ signaling has been shown to modulate basic G proteinactivated K + -channel GIRK [86] in response to e.g.…”
Section: Gα I3 Is Essential For Central Auditory Processingmentioning
confidence: 99%